Recital series for trombone or baritone with piano accompaniment includes solo parts in both treble and bass clefs - JOHNSON\'S, Clair W.. (Rubank Inc., 1968)
Red CanyonnFestive OdenPiece DramatiquenSolo ContrastsnDawn of Spring